If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -5y = 3x + -6 Reorder the terms: 8x + -5y = -6 + 3x Solving 8x + -5y = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8x + -3x + -5y = -6 + 3x + -3x Combine like terms: 8x + -3x = 5x 5x + -5y = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 5x + -5y = -6 + 0 5x + -5y = -6 Add '5y' to each side of the equation. 5x + -5y + 5y = -6 + 5y Combine like terms: -5y + 5y = 0 5x + 0 = -6 + 5y 5x = -6 + 5y Divide each side by '5'. x = -1.2 + y Simplifying x = -1.2 + y
| f(x)=5x^2-6x+2 | | 9x^2-2y^2=0 | | 5t-2(2t-3)=9t-18 | | [(3/(2x-1)^7] | | 220x^3-24x^2=0 | | 13+22=70 | | 140x^3+60x^2=0 | | v^2-2v-48= | | H(39)=2.59(39)+47.24 | | H(x)=2.59(46)+47.24 | | 2log(5x)+3log(x^4)=3 | | X^2=-qy | | 4x(x+3)-9=10x-8 | | 2xy+6xz=0 | | 5t^2+8t-15=0 | | -7x+2=3x-7 | | -1/2x-4=-6 | | 5k-5=42 | | -7x+0=3x-7 | | 3w-2=2 | | 2c+7=11 | | 5(7x+4)=-125 | | 2*log*2*x=13 | | -3k+3+5k=9 | | 2(1X+6)=10 | | -4m-1.1m+11+3.4m-16.1= | | 3(6-2y)-y=4 | | 5t^2+8t-10=0 | | -32=8-2k | | 1/x=213 | | 67=-3-10r | | h(t)=60x-16x^2 |